Vacinas contra Leishmaniose: uma revisão - Silva, Kathlenn Liezbeth de Oliveira [UNESP]; Santos, Diego Pacheco [UNESP]; Coelho, Natália Marinho Dourado [UNESP]; Silva, Deuvânia Carvalho [UNESP]; Okamoto, Ana Claudia [UNESP]; Gaetti-Jardim Júnior, Elerson [UNESP] (My University, 2013)
Leishmania is a protozoan belonging to the family Trypanosomatidae, obligate intracellular parasite cells of the mononuclear phagocyte system. In the New and Old World several orders of wild mammals (natural reservoirs) and various species of sandflies (vectors) are involved in the transmission of leishmaniasis. The new settlements in rural areas, changes in the environment and unplanned urbanization increased human contact with vector and interaction with the animal reservoir. A simple prophylactic measure seems to be the vector control as well as disease reservoir. With the goal of raising the prophylactic measures that are being used in vector control, the reservoir of the disease and what the infrastructure accordingly. We conducted a literature review in July 2011 in the electronic databases of Bireme, Medline, CancerLit, Portal Capes, SciELO, PubMed and Medscape, the main texts on the subject. Thus, the development of a vaccine that is effective against various forms of leishmaniasis in the old and new world, it is necessary and has been recommended by WHO as a possible tool for effective eradication of the disease.

Leishmania es un protozoo que pertenece a la familia de los Tripanosomátidos, obliga a las células de parásitos intracelulares del sistema de fagocitos mononucleares. En el Nuevo y Viejo Mundo en varios órdenes de mamíferos silvestres (reservas naturales) y varias especies de mosquitos (vectores) están involucrados en la transmisión de la leishmaniasis. Los nuevos asentamientos en las zonas rurales, los cambios en el medio ambiente y la urbanización no planificada con mayor contacto humano con el vector y la interacción con el reservorio animal. Una medida profiláctica sencilla parece ser el control de vectores, así como depósito de la enfermedad. Con el objetivo de aumentar las medidas profilácticas que se están utilizando en la lucha antivectorial, el reservorio de la enfermedad y lo que la infraestructura correspondiente. Se realizó una revisión de la literatura, en julio de 2011 en las bases de datos electrónicas de Bireme, Medline, CancerLit, Portal Capes, SciELO, PubMed y Medscape, los principales textos sobre el tema. Por lo tanto, el desarrollo de una vacuna que sea eficaz contra las diversas formas de leishmaniasis en el mundo antiguo y lo nuevo, es necesario y ha sido recomendado por la OMS como una posible herramienta para la efectiva erradicación de la enfermedad.

A Leishmania é um protozoário pertencente à família Trypanosomatidae, parasita intracelular obrigatório das células do sistema fagocítico mononuclear. No Novo e Velho Mundo diversas ordens de mamíferos silvestres (reservatórios naturais) e várias espécies de flebotomíneos (vetores) estão envolvidas na transmissão da leishmaniose. As novas colonizações em áreas rurais, mudanças no meio ambiente e urbanização não-planejada aumentaram o contato do homem com o vetor e a interação com o reservatório animal. Uma medida profilática simples parece ser o controle do vetor e também de reservatórios da doença. Com o objetivo de levantar as medidas profiláticas que estão sendo utilizadas no controle do vetor, no reservatório da doença e qual a infra-estrutura nesse sentido. Foi realizado um levantamento bibliográfico em julho de 2011 nas bases de dados eletrônicos do Bireme, Medline, Cancerlit, Portal Capes, Scielo, Medscape e PubMed, dos principais textos sobre o assunto. Sendo assim, o desenvolvimento de uma vacina que seja eficaz contra diferentes formas de leishmanioses, no Velho e no Novo Mundo, torna-se necessária e tem sido recomendada pela OMS como uma ferramenta possível para uma efetiva erradicação da doença.
Vaccines vs Leishmaniasis: a review
Vacunas contra la leishmaniasis: una revisión
Keywords: Prevention and control; Cntrol of communicable diseases; Leishmania; Vaccination; Prevención y control; El control de las enfermedades transmisibles; Leishmania; Vacunación; Prevenção e controle; Controle de doenças Transmissíveis; Leishmania; Vacinação